IMPROVING THE QUALITY OF ROUTINE DATA - Govender, Jegenthiren (My University, 2011)
Hospital Management Teams are expected to make crucial decisions in the short, medium and long term often based on questionable data. The integrity of decision-making is hence compromised by poor quality information. This report examines the interventions at a Public Hospital (GJ Crooke’s Hospital) to improve the quality of routine health data by focusing on systems, staff capacity and organisational culture. The methodology used was largely a qualitative approach together with simple elements of a quantitative approach in order to collect the required indepth information from targeted informants. Document reviews and observations augmented the information collected. The study shows that, at GJ Crooke’s Hospital, strong organisational information culture plays a major role in improving data quality, whilst partially integrated systems are detrimental to the quality of data. Focussed capacity building and the development, implementation and monitoring of a Data Management Policy will contribute further to enhancing data quality at the Hospital.
MM - P&DM
Keywords: Data quality at hospitals; Hospital management teams